Comparative Cytogenetics Analysis Among Peckoltia Species (Siluriformes, Loricariidae): Insights on Karyotype Evolution and Biogeography in the Amazon Region - Santos da Silva, Kevin; de Souza, Augusto Cesar Paes; Pety, Ananda Marques; Noronha, Renata Coelho Rodrigues; Vicari, Marcelo Ricardo; Pieczarka, Julio Cesar; Nagamachi, Cleusa Yoshiko (Frontiers in Genetics, 2021)
Peckoltia is widely distributed genus in the Amazon and Orinoco basins and the Guiana Shield, containing 18 valid species, and distinct morphotypes still needing description in the scientific literature due to its great taxonomic complexity. This study performed a comparative chromosomal analysis of two undescribed Peckoltia species (Peckoltia sp. 3 Jarumã and Peckoltia sp. 4 Caripetuba) from the Brazilian Amazon using conventional chromosome bands methods and in situ localization of the repetitive DNA (5S and 18S rRNA and U1 snRNA genes and telomeric sequences). Both species presented 2n = 52 but differed in their karyotype formula, probably due to inversions or translocations. The nucleolus organizer regions (NORs) showed distal location on a probably homeologous submetacentric pair in both species, besides an extra signal in a subtelocentric chromosome in Peckoltia sp. 4 Caripetuba. Heterochromatin occurred in large blocks, with different distributions in the species. The mapping of the 18S and 5S rDNA, and U1 snDNA showed differences in locations and number of sites. No interstitial telomeric sites were detected using the (TTAGGG)n probes. Despite 2n conservationism in Peckoltia species, the results showed variation in karyotype formulas, chromosomal bands, and locations of repetitive sites, demonstrating great chromosomal diversity. A proposal for Peckoltia karyotype evolution was inferred in this study based on the diversity of location and number of chromosomal markers analyzed. A comparative analysis with other Peckoltia karyotypes described in the literature, their biogeography patterns, and molecular phylogeny led to the hypothesis that the derived karyotype was raised in the left bank of the Amazon River.